PERSEPSI MASYARAKAT TERHADAP DAMPAK PETERNAKAN AYAM RAS PETELUR DI DESA SUMBERASRI KECAMATAN NGLEGOK KABUPATEN BLITAR - Moh Aris Triprastiya; Risma Novela Esti; Edya Moelia Moeis (AVES: Jurnal Ilmu Peternakan, 2022)
This study aims to determine the public's perception of the laying hens farming business in Sumberasri Village, Nglegok District, Blitar Regency. The material used in this research is people who live close to the laying hens farm environment. The research method used is a survey method, namely by taking a direct approach to the community around the location of the laying hens farm in Sumberasri Village, Kec. Look at Kab. Blitar. Based on the results of research that has been carried out in general, it can be concluded that the results of public perception of laying hens in Sumberasri Village, Nglegok District, Blitar Regency can be viewed from the aspect of smell, and the emergence of flies is actually not good (disturbed) but the community understands it. For water, soil and cage contamination, the community does not feel disturbed if it is handled properly. While the results of the study for the overall category got a score of 782, which means that the community does not feel disturbed by the existence of laying hens in Sumberasri Village, Nglegok District, Blitar Regency.